Effect of maternal dietary patterns on infant growth in Baotou, China - Jingyu Yang; Hailong Zhang; Mingming Han; Haiying He; Lin Xie (PLoS ONE, 2025)
Background Maternal dietary patterns (DPs) during pregnancy play a crucial role in fetal development and child growth. This study aims to investigate the association between maternal DPs and infant growth outcomes. Methods A prospective cohort study was conducted at The Third Hospital of Baogang Group from January 2020 to January 2022, enrolling 201 mother-child pairs. Maternal dietary intake during pregnancy was assessed, and DPs were identified using principal component analysis. Univariate analysis was performed to determine factors influencing maternal DPs. Infant weight and length were measured at birth and 12 months of age, and growth indicators including weight-for-age z-score (WAZ), height-for-age z-score (HAZ), and body mass index-for-age z-score (BMI Z) were calculated. The impact of maternal DPs on infant growth was analyzed by comparing growth outcomes across different DPs. Results Four distinct maternal DPs were identified: FMDP (high intake of fruits, milk, dairy products, and poultry), VBAP (vegetables, beans, algae, and pork), MP (marine products), and TE (tubers and eggs). Maternal education level was a significant factor influencing DP (P < 0.05). Higher adherence to FMDP and MP was associated with greater infant birth weight (P < 0.05), while VBAP was positively associated with birth weight (P < 0.05). Conversely, TE was linked to lower birth weight (P < 0.05). Additionally, FMDP was positively correlated with WAZ and HAZ at birth (P < 0.05), while MP was associated with higher WAZ at birth (P < 0.05). VBAP was positively associated with BMI Z at 12 months (P < 0.05), whereas TE was negatively associated with WAZ at birth (P < 0.05). Conclusion Maternal DPs during pregnancy significantly influence infant birth weight, length, and subsequent growth trajectories. These findings highlight the importance of maternal nutrition in offspring early-life growth and development.